Nephro-protective activity of wheatgrass juice against alcohol-induced oxidative damage in rats. (21st November 2020) - Hebbani, Ananda Vardhan; Bulle, Saradamma; Kanu, Venkateswarlu Reddy; Balachandrababu Malini, Asha; Reddy, Vaddi Damodara; Chakravarthula, Varadacharyulu Nallan
Abstract: The present study is an attempt to check the protective effect of fresh wheatgrass juice (WJ) as a potential therapeutic agent against alcohol-induced oxidative/nitrosative stress leading to nephrotoxicity in rats. Administration of 20% ethanol (5 g/kg b.wt/day) for 60 days resulted in a significant rise in the plasma concentrations of urea and creatinine with decreased levels of uric acid. Besides, a significant decrease in plasma electrolyte/mineral levels along with decreased activity of Na+/K+- ATPase activity was recorded in alcohol administered rats. In alcohol administered rats augmented lipid peroxidation (thio-barbituric acid reactive substance – TBARS) and nitric oxide (NOx) reflects the increased oxidative stress and nitrosative stress, moreover, we noticed a concomitant decrease in the levels of reduced glutathione (GSH) with decreased activities of antioxidant enzyme machinery viz ., superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR) and glutathione s-transferase (GST). Administration of WJ to the alcoholic rats significantly restored the plasma biochemical markers and the kidney antioxidant status near to control group animal levels. These findings were further confirmed by the kidney histopathological studies, wherein the protective effect of WJ treatment in retaining the morphological features of the renal tissue in spite of the alcohol administration was evident. The rich repertoire of phenolic compounds present in the WJ from the freshly sprouted seeds synergistically protected the kidney from alcohol-induced damage.